Media Pembelajaran Interaktif Berbasis Augmented Reality Pengenalan Anggota Tubuh dalam Bahasa Kutai untuk Sekolah Dasar Negeri 008 Samarinda Utara - Ahmad Sabirin; Heny Pratiwi; Yunita Yunita (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2026)
This study develops markerless Augmented Reality (AR) interactive learning media to introduce human body parts in the Kutai language as local content (Mulok) at SDN 008 Samarinda Utara. The primary issue stems from traditional methods—textbooks, 2D images, and conventional lectures—causing student boredom, low motivation, and shallow vocabulary mastery. This research aims to enhance learning motivation, conceptual understanding, and Kutai language proficiency through immersive experiences. The development follows the six-stage Multimedia Development Life Cycle (MDLC). The application was built on the Assemblr EDU platform (browser-based WebAR) using 3D models from Blender, interactive buttons, and Kutai language explanations. Black box testing was successful, while beta testing with ten students yielded an average score of 76.9% (Good category). This media supports immersive learning without additional installations, facilitating effective Mulok implementation at SDN 008. Future research is recommended to expand the respondent pool and integrate advanced interactive features, such as AR-based quizzes, audio narration, and animations, to further enhance overall media effectiveness. Exploring alternative platforms, including Unity and Zappar, is also encouraged. This tool represents a significant advancement in digitalizing regional language education, ensuring that local indigenous knowledge remains engaging and accessible for the younger generation in East Kalimantan.